Migration of a Needle From the Chest Wall Into the Right Ventricle in a 10-Year-Old Child. (November 2016) - Schultz, Jerette J.; Post, Megan E.; Plumley, Donald A.; O'Brien, Michael C.; DeCampli, William M.
Cardiac foreign bodies are rare in children and the nature or timing of the injury may be hard to ascertain. We report a case of a 10-year-old boy who presented with a 28-mm solid core needle in the left chest wall that advanced into his right ventricle, possibly from soft tissue manipulation. Computed tomography, intraoperative fluoroscopy, and echocardiography were necessary to locate the needle and successfully remove it surgically.